The effect of the mentoring model on improving the quality of life, mental health and training skills of newly-recruited teachers - Jaber Dadfar; Morteza Hazrati; Morad Rezaei Dizgah (Shahid Beheshti University of Medical Sciences, 2024)
Background: Teaching and professional development is one of the vital components in the educational process. The present study aimed to design a mentoring model to train newly recruited teachers to improve their quality of life and mental health. Methods: This explanatory and sequential study was conducted in the education organization of Gilan province in two qualitative and quantitative sections. In the qualitative section of the exploratory method, semi-structured interviews were conducted using purposeful sampling. Teachers with more than 20 years of experience, retired, clerics with more than 20 years of experience, senior managers, and newly recruited teachers were included in the study. Sampling continued until reaching a theoretical saturation (23 people). The statistical population in the quantitative stage included 265 people selected by stratified sampling. In the quantitative section, confirmatory factor analysis and LISREL software were used. Results: The thematic analysis method was used to analyze the interviews and qualitative results were designed as a thematic network, a global theme, 8 organizing themes, and 43 basic themes.  The organizing themes included the human elements of mentoring, educational, Islamic, structural, social, research, and mental health. In this section, the fit indices indicate the validity of an effective communication model with a mentoring approach, which was associated with improving teachers' quality of life and mental health. Conclusion: Human elements of mentoring, educational, structural, social, and research are crucial in mentoring newly recruited teachers. Thus, executives and relevant respondents should focus exclusively on implementing the research model.